2008
DOI: 10.1121/1.2967837
|View full text |Cite
|
Sign up to set email alerts
|

Modeling sound propagation in acoustic waveguides using a hybrid numerical method

Abstract: Sound propagation in an acoustic waveguide is examined using a hybrid numerical technique.Here, the waveguide is assumed to be infinite in length with an arbitrary but uniform crosssection. Placed centrally within the guide is a short component section with an irregular, nonuniform, shape. The hybrid method utilises a wave based modal solution for a uniform section of the guide and, using either a mode matching or point collocation approach, matches this to a standard finite element based solution for the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…One further issue with the hybrid method is the location of planes B and C. This has been discussed in detail for more complicated "obstacles" in acoustic waveguides by Kirby [17] and, in general, it was concluded that one should not locate these planes close to areas in which modal scattering is pronounced. This is because a modal solution often requires a proportionally larger number of modes to accurately represent a complex sound field when compared to the use of a standard finite element discretisation.…”
Section: Uncoated Pipementioning
confidence: 99%
See 2 more Smart Citations
“…One further issue with the hybrid method is the location of planes B and C. This has been discussed in detail for more complicated "obstacles" in acoustic waveguides by Kirby [17] and, in general, it was concluded that one should not locate these planes close to areas in which modal scattering is pronounced. This is because a modal solution often requires a proportionally larger number of modes to accurately represent a complex sound field when compared to the use of a standard finite element discretisation.…”
Section: Uncoated Pipementioning
confidence: 99%
“…For non-uniform discontinuities it is convenient to return to a full finite element discretisation of the defect in order to provide the flexibility to examine arbitrary (but axisymmetric) geometries. Accordingly, a hybrid method is adopted here, which follows the method described by Kirby [17] for acoustic waveguides. The advantage of this method is that it only requires a finite element discretisation of the non uniform defect and so retains the modal expansions within the uniform pipe sections.…”
Section: Hybrid Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid method implemented here follows the same general approach as that described by Kirby et al [21,22] for elastic waveguides, see also Kirby [18] and Duan and Kirby [19] for acoustic waveguides. Accordingly, a weak form of Eq.…”
Section: The Hybrid Methodsmentioning
confidence: 99%
“…One possible approach is to find the eigenmodes for a waveguide by directly solving the governing eigenequation. This method is often referred to in the elastodynamic literature as the semi analytic finite element (SAFE) method; however it has also been used in the acoustic waveguide literature where there is no such terminology [18,19]. A hybrid SAFE-FE method was recently applied to elastic wave propagation in a solid cylinder by Benmeddour et al [20].…”
Section: Introductionmentioning
confidence: 99%